Human embryonic stem cells recover in vivo acute lung inflammation bleomycin-induced - Sangiuolo, Federica; Spitalieri, P.; Quitadamo, M. C.; Orlandi, A.; Puxeddu, E.; Curradi, G.; Sangiuolo, F (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF)  is characterized by alveolar epithelial cell injury, type II cell activation, apoptosis and bronchiolar epithelial cell proliferation, accumulation of extracellular matrix and fibroblasts. No current animal model recapitulates all of these cardinal manifestation of the human disease. However, bleomycin instillation in mice lung by intranasal way (ITN) represents the best experimental model of pulmonary fibrosis in which alveolar pneumocytes type II (ATII) are usually depleted. The aim of this study was to test the possibility to recover acute lung fibrosis after transplantation of human embryonic type II derived-pneumocytes in a murine model of bleomycin-induced damage. Our results indicate the striking “clinical” beneficial effect of differentiated HUES-3 cells into ATII in terms of lung function, weight loss and mortality in injured mice, suggesting this stem cell therapy as a promising, systemic and specific treatment of human pulmonary fibrosis.